Formation of modern architectural concepts - V. N. Tkachev (Vestnik MGSU)
Introduction. The article addresses issues of methodological exchange in architectural studies and related fields of activities focused on problems of interaction between man and environment. The author makes a critical appraisal of leading modern trends in the architectural morphogenesis in foreign countries and Russia.Materials and methods. As a result of cross comparisons made within the framework of the study of theoretical publications and full-scale materials, now the human + environment binomial is the subject of research that synthesizes almost all theoretical developments as the main code of interaction. It is clear that lines of theory and practice have not coincided in ordinary and representative architecture for a long time, and architectural theory has been transformed into a scholastic visionary science that tends towards design. This is confirmed by professional publications and materials concerning existing and designed architectural facilities considered during the preparation of the article, as well as conceptual developments made by leading architects of our time.Results. The genetic sequence of trends in the formation of architectural stylistics typical for the most recent decades is presented in a condensed form, limited to mainstream works, while engineering characteristics of facilities are disregarded. The main creative lines and personalities of foreign “masters” of architecture are identified; present-day areas of research and the research methodology are correlated with their activities.Conclusions. A fundamental difference is identified between social prerequisites and vectors of architectural development in Russia and worldwide. Characteristics of positive and negative manifestations of evolution of global architecture are listed. A tendency towards formation of a paradigm of “intellectual architecture”, morphological and technological choice of “pure forms”, minimalism in aesthetic programs of architecture, greater importance of principles of expediency, industrialization, standardization in design are identified; hypotheses are made in order to solve problems of human-computer polarization in the future profession of an architect.